Empiric: A Card Game for Guideline-Based Antibiotic Prescribing Used for Continuing Medical Education - Michael Cosimini; Diego Molina Ochoa; Diana Yu; Alison Chiang (MedEdPORTAL)
Introduction Adherence to guidelines when prescribing antibiotics can reduce antibiotic resistance and prevent adverse patient effects. However, adherence in practice is mixed. Nonadherence can be partly attributed to a lack of knowledge or understanding of guidelines. Tabletop games promote active learning of guidelines in an engaging, psychologically safe manner. While card and board games for medical education are gaining popularity, they generally target early learners. This novel workshop instead targets practitioners pursuing CME and demonstrates the utility of games for learning in a new audience. Methods A card game using a scoring system designed to emphasize the use of narrow-spectrum antibiotics and observation without antibiotics was developed iteratively over 5 years. The game was used in a series of primary care CME conferences, and evaluations were collected to assess the efficacy of the presentation and how it would impact behavior change. Results Fifty-four practicing primary care providers participated in workshops using this game over the course of two regional CME conferences. Using a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree), participants rated the workshop highly in all categories, including “I will make changes in my work or practice based on the information presented.” Qualitative comments were positive, highlighting that the workshop was “helpful” and “fun.” Discussion This workshop shows that CME audiences are receptive to games and could find them useful. Serious games for CME should continue to be explored, including for educational efficacy and best practices in the pairing of educational content and game mechanics.